Integrated Eco-design Decision-making for Sustainable Product Development - Awanis, Romli; Prickett, Paul; Setchi, Rossitza; Soe, Shwe (Taylor & Francis, 2015)
This paper presents an integrated eco-design decision-making (IEDM) methodology that is formed using three stages: life cycle assessment, an eco-design process (Eco-Process) model and an enhanced eco-design quality function deployment process. All product sustainability considerations are conducted within a special eco-design house of quality. This brings together the analysis of factors relating to manufacturing processes, product usage and end-of-life strategy. The concentration of environmental considerations in one place insures that product sustainability is central to any design development and that the implications of change are fully identified and justified. The IEDM methodology utilises of a set of Eco-Process parameters and their associated relationships to allow users with complementary knowledge to enter and access information in a timely and controlled manner. They are then able to contribute their expertise to support decisions with the aim of providing more sustainable products. An application of the approach is presented in the context of a case study considering the redesign of a single-use medical forceps. The materials and production methods used are investigated with a view to quantifying their environmental impact. The resulting IEDM methodology can be seen to be widely and easily applicable.